The development of port emissions inventory from decision-making perspective: case of the port of Los Angeles. Issue 1 (February 2021) - Cai, Ouchen; Peng, Chuansheng; Yu, Xiujuan
Abstract: The article, based on the comprehensive review and the case study of Port of Los Angeles, investigates the driving force for the development of the port emissions inventory in numerous aspects including environment, public health, economy and society. It includes the summary of the typical methodology for establishing the port emissions inventory, thus allowing the policy makers from more ports including port authorities and operators with no such expertise or experience obtain the insights in terms of strategy, policy and technology which may inspire them to develop their own emission inventories which could be the foundation for decision making related to the emission control and reduction. In addition, the article analyzes the performance of the inventory in facilitating designing the air pollution management measures against various emission sources, especially the critical air emissions from the ocean-going vessels causing significant negative effects in port and coastal areas.